Satisfação dos cuidadores familiares à intervenção de telerreabilitação e de acompanhamento para pessoas idosas com demência: ensaio clínico randomizado - Gerassi, Renata Carolina (2023)
Among the so-called chronic non-communicable diseases and syndromes that commonly affect older people, dementias stand out, for having characteristics that do not affect only the sick individual. They extend to the entire family structure and to society, with great psychosocial and economic impact. Faced with social distancing as a protective measure against the pandemic of COVID-19, many older people and caregivers have had to learn to deal with the use of Information and Communication Technologies. Tele-rehabilitation is a long-distance health care access alternative that has been used extensively during the pandemic of COVID-19 and can help access health care and quality of life for older adults with dementia and their caregivers without posing a risk of contagion from COVID-19. The satisfaction factor with telerehabilitation is an important focus of research, as it is a key aspect to measure the quality of care and assess the relevance of these services provided. The present study aimed to verify caregiver satisfaction to a Telerehabilitation Program and to Remote Follow-up in older adults with dementia and their caregivers; to compare caregiver satisfaction to telerehabilitation and Remote Follow-up in older adults with dementia and their caregivers during social distancing by the COVID-19 pandemic; To verify which factors interfere in the caregiver's satisfaction to the interventions, including the factors related to the older adults with dementia (age, sex, comorbidities, mental health status - cognition and behavior and functional capacity) and factors related to the caregiver (age, sex, years of study, marital status, family monthly income, whether he/she shares the care with someone else and how many hours of the day care is given to the older adults, mental health status - cognition and behavior, quality of life and burden). This research has a quanti-qualitative approach and is part of a randomized clinical trial only post-test with a control group, with blinding of the evaluator, controlled by two groups: Intervention Group (Telerehabilitation Program) and Control Group (Remote Follow-up). Caregivers in both groups received information in a standardized manner about dementia and COVID-19 care at baseline. For the Intervention Group, this information was more detailed and after these presentations, the Intervention Group received the Telerehabilitation Program, with standardized exercise for the older adults and guidelines for the caregiver. There were two online assessments: initial and after 12 weeks. The initial assessment was intended to measure mental health status (cognition and behavior) and functional capacity. In addition, mental health status, quality of life, and caregiver burden were assessed. After 12 weeks, caregiver satisfaction to the intervention and to Remote Monitoring in the older adults was verified using an online questionnaire. For the analyses, a significance level of α = 0.05 was adopted and SPSS (20.0) software was used to perform the statistical tests. For the open-ended questions, the procedure of qualitative data treatment and analysis was adopted, using the MAXQDA2022 software. After coding, for the obtained segments, Bardin's content analysis technique was performed. The total final sample after 12 weeks comprised 64 pairs of family caregivers and older persons. Caregivers in the Telerehabilitation Program showed higher satisfaction with the intervention, with the Internet treatment, and with the health care received than caregivers submitted to the Remote Follow-up. Both groups reported that they liked the treatment, pointed out the audio and video quality as excellent, and signaled a preference for Internet treatment over face-to-face. In the Intervention Group, only the hours dedicated to care influenced the satisfaction with the intervention. In the Control Group, the performance in cognition and functionality of the older person influenced satisfaction with the Remote Follow-up. More caregivers in the Intervention Group had their expectations reached, compared to the Control Group, although both groups reported difficulties throughout the 12 weeks and suggestions to the treatment. We conclude that the telerehabilitation program achieved satisfactory results, suggesting the potential of telerehabilitation as an aid in providing care for the older person with dementia and their caregivers.